Kunci sukses memasarkan jasa pariwisata / Rio Budi Prasadja Tan ; editor Niken Hananti ; Daniel P. Purba. - RIO BUDI PRASADJA TAN; Niken Hananti; Daniel P. Purba (Esensi, 2010)
172 hlm. : ilus. ; 26 cm [3 eks.]